Quality Management in Public Service - Topár, József (Theory, Methodology, Practice – Review of Business and Management, 2007)
Nowadays the efficient use of quality management systems and methods is becoming an important requirement in the institutions operating in the field of public services. The article deals with some elements of the quality efforts in public health, public administration and higher education. My aim is to give an overview of the most important features and operational pieces of experience of quality management systems in the public services in order to make the institutions of these sectors able to adapt those quality management approaches, systems and methods which meet the requirements of their clients and of the organization.